2015
DOI: 10.1007/s12038-014-9492-2
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet releasates combined with polyglycolic acid scaffold promote chondrocyte differentiation and phenotypic maintenance

Abstract: In the present study, we aimed to demonstrate the differentiating properties of platelet-rich plasma releasates (PRPr) on human chondrocytes seeded on a polygtlycolic acid (PGA) 3D scaffold. Gene expression and biochemical analysis were carried out to assess the improved quality of our PGA-based cartilage constructs supplemented with PRPr. We observed that the use of PRPr as cell cultures supplementation to PGA-chondrocyte constructs may promote chondrocyte differentiation, and thus may contribute to maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(50 reference statements)
2
7
0
Order By: Relevance
“…For transfusion purposes, blood is usually collected in bags containing citrate phosphate dextrose adenine (CPDA-1) solution, as anticoagulant [ 22 , 23 ], from which a platelet concentrate is obtained by double centrifugation of the whole blood or apheresis. Platelets concentrates obtained by such methodologies may also be used for promoting tissue repair [ 24 ]. On the other hand, recent PRP formulations for autologous applications are usually prepared in collection tubes containing citrate solutions, in the form of sodium citrate [ 25 29 ] or ACD-A [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…For transfusion purposes, blood is usually collected in bags containing citrate phosphate dextrose adenine (CPDA-1) solution, as anticoagulant [ 22 , 23 ], from which a platelet concentrate is obtained by double centrifugation of the whole blood or apheresis. Platelets concentrates obtained by such methodologies may also be used for promoting tissue repair [ 24 ]. On the other hand, recent PRP formulations for autologous applications are usually prepared in collection tubes containing citrate solutions, in the form of sodium citrate [ 25 29 ] or ACD-A [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autologous Chondrocyte Implantation (ACI) has proven to be a pivotal approach as restorative cartilage surgery. However, even the most recent ACI techniques have some limitations 33 . It has been shown that the transplanted chondrocytes are able to form new cartilage, which appears to be of hyaline nature and expresses typical cartilage markers such as type II collagen, aggrecan and COMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated aliphatic polyesters, such as poly(glycolic acid) (PGA), PLA, and PLGA copolymers, are the most often used biodegradable synthetic polymers for 3D scaffolds in tissue engineering. 207 211 The chemical properties of these polymers allow hydrolytic degradation through de-esterification. For example, PLA and PGA can be processed easily, and their degradation rates and physical and mechanical properties are adjustable over a wide range by using various molecular weights, structure, composition, and copolymers.…”
Section: Synthetic Biodegradable Polymersmentioning
confidence: 99%
“…For example, PLA and PGA can be processed easily, and their degradation rates and physical and mechanical properties are adjustable over a wide range by using various molecular weights, structure, composition, and copolymers. 207 , 208 , 211 Moreover, the body contains highly regulated mechanisms for completely removing monomeric components of glycolic and lactic acids when these polyesters degrade: glycolic acid is converted to metabolites or eliminated by other mechanisms, whereas lactic acid can be cleared through the tricarboxylic acid cycle. 212 Due to their biodegradability and biocompatibility, PGA and PLA have been approved by the FDA for use in medical devices, such as degradable sutures and other implantable devices.…”
Section: Synthetic Biodegradable Polymersmentioning
confidence: 99%